Monitoring and controlling aspiration fluid temperature during ovum pick-up in southern white rhinoceros (Ceratotherium simum simum) - Holm, Dietmar Erik (University of Pretoria, 2023)
Dissertation (MSc (Veterinary Science))--University of Pretoria, 2022.